The Little Mermaid [videorecording (DVD)] : a ballet - Neumeier, John, 1939-; Tan, Yuan Yuan; Riggins, Lloyd; Helimets, Tiit; Tomasson, Helgi, 1942-; Andersen, H. C. (Hans Christian), 1805-1875; Auerbach, Lera (C Major Entertainment, 2011)
In The Little Mermaid, Hamburg ballet director and chief choreographer John Neumeier blends dance, dramatic storytelling and spectacle into a stunning interpretation of Hans Christian Andersen's fable.